2024
DOI: 10.1111/nph.19560
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza convey significant plant carbon to a diverse hyphosphere microbial food web and mineral‐associated organic matter

Anne Kakouridis,
Mengting Yuan,
Erin E. Nuccio
et al.

Abstract: Summary Arbuscular mycorrhizal fungi (AMF) transport substantial plant carbon (C) that serves as a substrate for soil organisms, a precursor of soil organic matter (SOM), and a driver of soil microbial dynamics. Using two‐chamber microcosms where an air gap isolated AMF from roots, we 13CO2‐labeled Avena barbata for 6 wk and measured the C Rhizophagus intraradices transferred to SOM and hyphosphere microorganisms. NanoSIMS imaging revealed hyphae and roots had similar 13C enrichment. SOM density fractionation,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 134 publications
0
1
0
Order By: Relevance
“…Additionally, AMF play a crucial role in transporting significant amounts of photosynthetic carbon to the soil. This carbon is either occluded within soil aggregates or stabilized in mineral-associated organic matter, thereby enhancing carbon sequestration (Kakouridis et al, 2024 ). The research findings have indicated variations in AMF among functionally distinct groups of plants.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, AMF play a crucial role in transporting significant amounts of photosynthetic carbon to the soil. This carbon is either occluded within soil aggregates or stabilized in mineral-associated organic matter, thereby enhancing carbon sequestration (Kakouridis et al, 2024 ). The research findings have indicated variations in AMF among functionally distinct groups of plants.…”
Section: Resultsmentioning
confidence: 99%